Application and optimization of prostate-specific antigen screening strategy in the diagnosis of prostate cancer: a systematic review - Zhang, Zhengchao; Tian, Aimin; Che, Jizhong; Miao, Yandong; Liu, Yuanyuan; Liu, Yangyang; Xu, Yankai (Frontiers in Oncology, 2024)
Currently, prostate cancer (PCa) poses a global risk to the well-being of males. Over the past few years, the utilization of prostate-specific antigen (PSA) screening has become prevalent in the identification and management of PCa, which has promoted a large number of patients with advanced PCa to receive timely treatment and reduce the mortality. Nevertheless, the utilization of PSA in PCa screening has sparked debate, and certain research has validated the potential for overdiagnosis and overtreatment associated with PSA screening. Hence, in order to decrease the mortality rate of PCa patients and prevent unnecessary diagnosis and treatment, it is crucial to carefully choose the suitable population and strategy for PSA screening in PCa. In this systematic review, the clinical studies on PSA screening for the diagnosis and treatment of PCa were thoroughly examined. The review also delved into the effects and mechanisms of PSA screening on the prognosis of PCa patients, examined the factors contributing to overdiagnosis and overtreatment, and put forth strategies for optimization. The objective of this research is to offer valuable recommendations regarding the utilization of PSA screening for the detection and management of PCa.